Peran Agama dalam Membentuk Kesehatan Mental Remaja - Yasipin Yasipin; Silvia Ayu Rianti; Nurman Hidaya (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2023)
Abstract: Religion Role for The Health of Teenager mental. The purpose of writing to describe and find out how to improve the character of the nation based on Evidence Based. This research is a library research that uses written material taken from several literatures, in the process of searching literature used several databases such as Pubmed, NCBI, Google scholar and sciencedirect. Conclusion 1). Mental health can affect the condition of one's mind, feelings and mood 2). As a result of mental health disorders cause a person to be ineffective 3). Mental health problems can be overcome by religious therapy 4). Dhikr can make someone relax. 5). The higher the understanding of one's religion, the more healthy the mental condition.